Oral impacts on Daily Performances Related to Wearing Orthodontic Appliances among the Patients Reporting to the Department of Orthodontics and Dentofacial Orthopaedics, Dhaka Dental College and Hospital (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2018)
Introduction: Patients may have some oral impacts on their day to day activities during the course of treatment with orthodontic appliances. Often the impacts may lead the patient to interrupt or terminate the treatment. Proper information on frequency, intensity and extent of the oral impacts on daily performances related to wearing orthodontic appliances during orthodontic treatment will help the patient and orthodontists to increase the treatment compliance.Objectives: To assess the frequency, severity and extent of oral impact on daily performances (OIDP) im the patients wearing orthodontic appliances in relation to type of orthodontic appliancea and sex of patients.Materials and method: The study was a descriptive cross sectional study with 300 participants by convenient sampling aged 10-25 years, undergoing orthodontic treatment at the department of Orthodontics & Dentofacial Orthopedics of Dhaka Dental College & Hospital. Face-to-face structured interviews and clinical examination were done to collect information about OIDP.Results: Three hundred patients (31% male and 69% female) undergoing orthodontic treatment participated in the study. The prevalence of condition-specific impacts related to wearing orthodontic appliances was 31.7%. Among adolescents with impacts related to wearing orthodontic appliances, 17.8% reported impacts of severe or very severe intensity and 90.5% reported impacts on only one daily performance, commonly eating or speaking or cleaning mouth. The prevalence and the extent, but not the intensity of condition-specific impacts differed by type of orthodontic appliance (P =.002* and .004* respectively).Conclusion: Almost one in three participants undergoing orthodontic treatment reported side effects, specific impacts on daily living related to wearing orthodontic appliances. Such impacts were higher among patients wearing fixed and combination of both fixed and removable type of orthodontic appliances rather than removable type. This information could help to inform patients about the frequency and intensity of sociodental impacts during the course of their treatment.Ban J Orthod & Dentofac Orthop, April 2015; Vol-5 (1-2), P.1-7